Politeness Maxim Violations in the Japanese Variety Show “Sake No Tsumami Ni Naru Hanashi” - Amalia, Ilma; Ali, ​Mohammad (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
This study examines violations of politeness principles by Geoffrey Leech (1983) on a Japanese variety show called "Sake no Tsumami ni Naru Hanashi". The study uses an approach to understand politeness based on what Geoffrey Leech said, which includes six maxims: tactful, generous, approbation, agreeing, modesty, and empathy. The study uses a method to describe what is the real meaning behind the violation. The information was collected from one episode of the show that aired on Fuji TV. The participants on the show were talking casually. The study looked at what they said.The results show that participants on the show are often not polite when they talk to each other. There were 20 times when participants said something that was not polite according to Leech's theory. Most of the time, participants did not agree with each other. Sometimes they were not tactful or humble. When participants were not polite on the show, it was usually to make audiens laugh and keep the show entertaining. So being impolite on this show was not meant to cause problems. To make the show funny and interesting. The "Sake no Tsumami ni Naru Hanashi" show uses violations to make people laugh, and that is what makes it entertaining.